Prevalence, classifications and factors associated with sexual dysfunction among adult cancer patients on chemotherapy at the Uganda Cancer Institute, Mbarara - Oenga, Joel Nyanchiri; Tamukong, Robert; Isiiko, John; Gibu, Sibali Gidimali; Gidion, Kule; Yadesa, Tadele Mekuriya (BMC Cancer, 2024)
Background: Sexual dysfunction is a social challenge that devastates many people, including cancer patients. However, among the numerous reported side effects of chemotherapy sexual dysfunction is the least studied and reported. The chemotherapeutics used among cancer patients are potential risk factors for the development of sexual dysfunction, and such an understanding of these risk factors can lead to numerous interventions to bypass their effects on sexual activity. Objective The goal of this study was to determine the prevalence, classification and factors associated with sexual dysfunction among cancer patients receiving chemotherapy. Methods: A cross-sectional study was conducted among 214 cancer patients at the Mbarara Regional Referral Hospital in southwestern Uganda for a period of 3 months from August to October 2023. A systematic sampling technique was employed in the study; a questionnaire was used to collect patient data. The standardized female sexual function index and international index of erectile function tools were used to classify types of sexual dysfunctions among women and men, respectively. Sexual dysfunction-associated factors were analyzed by logistic regression using Stata version 17. Results: A total of 127 males and 87 females with a median age of 50 years were enrolled. Overall (42.1%) of the patients, (54.3%) males and (24.1%) females experienced sexual dysfunction. (33.9%) of male reported overall sexual dissatisfaction, while among female (18.4%) patients reported decreased sexual desire. while others reported reduced arousal and vaginal pain. Multivariate logistic regression revealed the following independent risk factors for sexual dysfunctions: male sex (AOR 3.99, 95% CI 1.93–8.25; p value = 0.001), gastrointestinal cancer (AOR 3.46, 95% CI 1.34– 8.93; p value = 0.010) and anthracyclines use (AOR 4.26, 95% CI 1.02, 17.76; p value = 0.047). Conclusions: Our findings suggest that there is a high prevalence of sexual dysfunction among cancer patients at the Mbarara Regional Referral Hospital. In male patients, overall sexual dissatisfaction is the most prevalent, while decreased sexual desire is prevalent in females. Routine screening of sexual functions should be encouraged for all patients receiving chemotherapies. Males patients, those diagnosed with gastrointestinal cancers and those receiving regimens containing anthracyclines should be more closely monitored for sexual dysfunction.
Keywords: Anorgasmia; Dyspareunia; Erectile dysfunction; Anthracyclines; Chemotherapy